The Influence of Product Quality and Brand Image on Repurchase Intention Through Customer Satisfaction as an Intervening Variable (A Study on Kopi Kenangan Customers in Surabaya) - Stephanie Zefanya Sitompul; Sonja Andarini (Indonesian Interdisciplinary Journal of Sharia Economics, 2025)
Currently, the food and beverage industry is growing rapidly in Indonesia, particularly the coffee beverage business. Kopi Kenangan is one of the fastest-growing retail coffee businesses in Indonesia. This study aims to analyze the influence of Product Quality and Brand Image on Repurchase Intention, with Customer Satisfaction as an intervening variable among Kopi Kenangan customers in Surabaya. The research employs a quantitative method, with data collected through questionnaires. The sampling technique used is purposive sampling, with a total of 150 respondents. The sample criteria include Kopi Kenangan customers residing in Surabaya, aged at least 17 years, and having purchased and consumed Kopi Kenangan products at least twice. Data analysis was conducted using SmartPLS 3.0 to examine the relationships between variables. The results show that Product Quality does not have a direct influence on Repurchase Intention, whereas Brand Image has a significant effect on Repurchase Intention. Furthermore, Product Quality significantly affects Customer Satisfaction, and Brand Image also has a significant impact on Customer Satisfaction. Customer Satisfaction is also proven to mediate the relationship between Product Quality and Brand Image with Repurchase Intention. In other words, although Product Quality does not directly increase Repurchase Intention, Customer Satisfaction can act as a bridge in this relationship. These findings have implications for Kopi Kenangan in enhancing customer loyalty by strengthening Brand Image and ensuring customer satisfaction after consuming the product.